Magnetic resonance imaging quantification of fasted state colonic liquid pockets in healthy humans - Murray, Kathryn; Hoad, Caroline L.; Mudie, Deanna M.; Wright, Jeff; Heissam, Khaled; Abrehart, Nichola; Pritchard, Susan E.; Al Atwah, Salem; Gowland, Penny A.; Garnett, Martin C.; Amidon, Greg E.; Spiller, Robin C.; et al. (American Chemical Society, 2017)
The rate and extent of drug dissolution and absorption from solid oral dosage forms is highly dependent on the volume of liquid in the gastrointestinal tract (GIT). However, little is known about the time course of GIT liquid volumes after drinking a glass of water (8 oz), particularly in the colon, which is a targeted site for both locally and systemically acting drug products. Previous magnetic resonance imaging (MRI) studies offered novel insights on GIT liquid distribution in fasted humans in the stomach and small intestine, and showed that freely mobile liquid in the intestine collects in fairly distinct regions or “pockets”. Based on this previous pilot data, we hypothesized that (1) it is possible to quantify the time course of the volume and number of liquid pockets in the undisturbed colon of fasted healthy humans following ingestion of 240 mL, using noninvasive MRI methods; (2) the amount of freely mobile water in the fasted human colon is of the order of only a few milliliters. Twelve healthy volunteers fasted overnight and underwent fasted abdominal MRI scans before drinking 240 mL (∼8 fluid ounces) of water. After ingesting the water they were scanned at frequent intervals for 2 h. The images were processed to quantify freely mobile water in the total and regional colon: ascending, transverse, and descending. The fasted colon contained (mean ± SEM) 11 ± 5 pockets of resting liquid with a total volume of 2 ± 1 mL (average). The colonic fluid peaked at 7 ± 4 mL 30 min after the water drink. This peak fluid was distributed in 17 ± 7 separate liquid pockets in the colon. The regional analysis showed that pockets of free fluid were found primarily in the ascending colon. The interindividual variability was very high; the subjects showed a range of number of colonic fluid pockets from 0 to 89 and total colonic freely mobile fluid volume from 0 to 49 mL. This is the first study measuring the time course of the number, regional location, and volume of pockets of freely mobile liquid in the undisturbed colon of fasted humans after ingestion of a glass of water. Novel insights into the colonic fluid environment will be particularly relevant to improve our understanding and design of the in vivo performance of controlled release formulations targeted to the colon. The in vivo quantitative information presented here can be input into physiologically based mechanistic models of dissolution and absorption, and can be used in the design and set up of novel in vitro performance tools predictive of the in vivo environment.